Modifying creation?: an Evangelical Alliance Policy Commission report - Bruce, Donald; Horrocks, Donald L. (Paternoster Press, 2001)
Introduction -- What is genetic modification? The science of plant breeding and genetic modification -- Is it wrong to do genetic modification? Theological reflections on genetic modification of crops and food -- Is genetic modification too risky? Environmental and health risks of GM crops -- Does the UK need GM crops? The impact of GM on UK agriculture -- What sort of farming should we adopt? Should we go organic, GM, or what? -- Is GM just a powerful tool in the hands of the powerful? The power structures which drive GM crop technology -- Is GM needed in the developing world? Motives, accountability and priorities -- Reflections: How should we evaluate GM crops and food? -- Resolutions and affirmations of the Evangelical Alliance Policy Commission relating to GM crops and food : conclusions and recommendations